Strong reorganization of multi-domain microbial networks associated with primary producers sedimentation from oxic to anoxic conditions in an hypersaline lake. Issue 12 (16th December 2021) - Escalas, Arthur; Troussellier, Marc; Melayah, Delphine; Bruto, Maxime; Nicolas, Sébastien; Bernard, Cécile; Ader, Magali; Leboulanger, Christophe; Agogué, Hélène; Hugoni, Mylène
ABSTRACT: Understanding the role of microbial interactions in the functioning of natural systems is often impaired by the levels of complexity they encompass. In this study, we used the relative simplicity of an hypersaline crater lake hosting only microbial organisms (Dziani Dzaha) to provide a detailed analysis of the microbial networks including the three domains of life. We identified two main ecological zones, one euphotic and oxic zone in surface, where two phytoplanktonic organisms produce a very high biomass, and one aphotic and anoxic deeper zone, where this biomass slowly sinks and undergoes anaerobic degradation. We highlighted strong differences in the structure of microbial communities from the two zones and between the microbial consortia associated with the two primary producers. Primary producers sedimentation was associated with a major reorganization of the microbial network at several levels: global properties, modules composition, nodes and links characteristics. We evidenced the potential dependency of Woesearchaeota to the primary producers' exudates in the surface zone, and their disappearance in the deeper anoxic zone, along with the restructuration of the networks in the anoxic zone toward the decomposition of the organic matter. Altogether, we provided an in-depth analysis of microbial association network and highlighted putative changes in microbial interactions supporting the functioning of the two ecological zones in this unique ecosystem. Abstract : In-depth analysis of microbial networks from the three domains of life reveals how reassociations between microorganisms support the functioning of an hypersaline and hyperalkaline crater lake.